DEVELOPMENT AND VALIDATION OF SCALE ON ACADEMIC STRESSORS IN COLLEGE STUDENTS: A FACTOR ANALYTICAL APPROACH - Jabeen, Ayesha; Shahzad, Aiman; Khan, Maria (Journal of Postgraduate Medical Institute, 2024)
Objective: To find out the experience and expression of academic stressors in college students and to develop a reliable and valid measure. Methodology: A sample of 244 college students with age range 15-20 (M = 17.38, SD = 1.22) were selected through the convenient sampling technique. Both boys and girls living in intact families, having no physical or psychological disorder studying in different government and private institutes of city Lahore were included in the study. A three-step model (item generation, expert validation, and pilot study) was used to develop the scale. Results: Descriptive statistics revealed n=97(39%) 1st year and 147 (61%) 2nd year students with highest number living in nuclear family system (n=150 (61%). Exploratory factor analysis using Principal Component factor analysis revealed two factors: sustaining performance and psychosocial stressors. The value of Kaiser-Meyer-Olkin was .87and the Bartlett test was 929.90 with p=0.000. Student Problem Checklist was used to establish the concurrent validity of the scale and was found to be r=.92. The internal consistency was 0.92 (p<0.001) and the test-retest reliability of ASS was r=.67 (p<0.001). Girls experienced more academic stressor (M=35.53,SD=19.43, p<0.001) as compared to boys (M=31.72,SD=13.45) Conclusion: The Academic Stressor Scale is an indigenous scale with established psychometrics that provides a depiction of academic stressors faced by Students in Pakistani culture.